Algunas aproximaciones a la educación primaria para jóvenes y adultos en la provincia del Chaco - Blazich, Gladys Susana (2012)
This article presents some results of a research carried out in a primary school for young people and adults located in the city of Resistencia, Chaco, Argentina. The purpose of this educational research was to register the opinions of teachers about their students and young adults; to get closer to their educational practices through a survey that could recover their stories; and identify possible relationships between these concepts and methodological criteria selected for their pedagogical task. The methodology used was a qualitative approach rooted in ethnography, based on in-depth interviews. The analysis identified that students are characterized by their shortcomings and that the social and cultural situation of them guide teachers educational practices. Regarding the methodological criteria teachers selected for classroom intervention seem grounded in pragmatic actions that do not recognize the pedagogical foundations of teaching and learning. The pedagogical task that develops from the institution, doesn’t allow , in any way questions, not even reflect the conditions in which the exclusion of these adults occurs and therefore, the tools provided to change the situation in which they find themselves, are insufficient.